Lifestyle habits among Najran University students, Najran, Saudi Arabia - Awad Mohammed Al-Qahtani (Frontiers Media S.A., 2022)
BackgroundUnhealthy lifestyles have been linked to increased cardiovascular disease, diabetes, and other non-communicable diseases. University students have been reported to adopt unhealthy lifestyles and undesirable eating choices.ObjectivesThe study aimed to estimate the prevalence of healthy eating habits; determine the prevalence of physical activity habits; to estimate the smoking habits among male health sciences college students at Najran University, Najran, Saudi Arabia.MethodsThe present questionnaire-based descriptive cross-sectional study (convenient sample) was carried out among undergraduate male students enrolled in the health sciences colleges at Najran University, Najran, Saudi Arabia, from 1st May to 31st May, 2019. Around 500 students were recruited and were requested to answer a self-administered questionnaire about eating habits, physical activity, and tobacco smoking habits. Descriptive results were summarized in percentage and frequency. Cross tabulation using chi-square test was performed to measure the impact of demographic variable on eating pattern, physical activity and smoking behavior. Pearson's correlation was done using two tailed tests to determine the type of relationship between different variables. The SPSS (version 26) was used to perform statistical analysis.ResultsA total of 454 complete responses from the male students from Najran University were obtained. The majority (74%) were aged 21 years and above, unmarried (94.9%), had healthy BMI (47.4%), and suffered mild (41.4%) to moderate (32.4%) levels of stress during the previous month. The study findings showed a low daily frequency of consumption of vegetables and fruits. There was a low prevalence of daily consumption of vegetables (16%) and fruits (9%). More than 10% of all students reported no consumption of fruits and vegetables. Students who felt severely stressed during the previous month were significantly not eating any vegetables (p = 0.022) and fruits (p < 0.001), and had high salt intake (p = 0.045). Married participants had a significantly (p = 0.03) higher servings of vegetables per day. Furthermore, 32.15% of participants were not practicing 30 min of physical activity 5 days per week. The study showed a low prevalence (47.57%) of physical activity among the participants. However, none of the participants' variables were significantly associated with routine physical activity. In addition, the study showed a relatively high prevalence of smoking (25.77%) among Najran university male students. The participants' age (p 0.01), overall health (p = 0.02) and level of stress (p = 0.001) experienced during the last month were significantly associated with the length of exposure to secondhand smoke. Whereas, smoking any kind of tobacco daily (25.77%) was significantly (p = 0.005) related to the age of participants. A high number of participants aged 21 years and above (52.72%) were significantly (p = 0.019) exposed to secondhand smoke.ConclusionTo conclude, the study findings showed a low daily frequency of consumption of vegetables and fruits, a relatively high prevalence of smoking and a low level of awareness regarding the health risks of smoking; and a large number of participants were physically inactive among male university students. Intervention programs in university students should concentrate on improving nutrition attitudes and knowledge toward good diet, tobacco-smoking cessation strategies, and structured intervention programs to encourage physical activity. However, these interventions should be pilot-tested for feasibility and acceptability before implementation.